Formas de Obtención de semilla de papa super chola en el sector de la Purificacion, Cantón Huaca - Mafla Rosales, Henry Santiago (2019)
SUMMARY In the San Pedro de Huaca canton the research was carried out to know the ways of obtaining seeds of the potato (Solanum tuberosum) in the super chola variety, this research is directed to know why there is a degradation of the seeds manifesting in low yields, plants less resistant to diseases and pests and a discoloration in the tuber, to achieve this, an introduction was presented in chapter I in which we expose important data on potato cultivation as well as the demand for certified seeds In the country, we finished this section by determining the following specific objectives: 1) Investigate the ways of obtaining seed of potato at the level of qualified breeders, 2) Determine the procedure used by farmers in the Huaca Canton Purification sector to obtain the seed potato super chola. 3) Establish the causes so that certified seed is not used in potato crops by farmers in the Huaca Purification Canton sector. Chapter II contains the documentary and bibliographic information of the main concepts that are handled within the investigation. The content of chapter III has to do with the main materials used for the development of the research and the methodology to be followed is formulated. In this case, methods such as qualitative analysis and observation are used, the technique used to collect information is the interview. Chapter IV presents the results achieved which show that the means of obtaining seeds most used by farmers are informal and formal. To finish in chapter V, the conclusions reached after analyzing the information together with their respective recommendations issued to improve the cultivation of potatoes in the investigated sector are presented. Keywords: potato, seed, certified, production, crop, hydroponic, variety, price, aeroponic,plants.